2019
DOI: 10.1093/beheco/arz116
|View full text |Cite
|
Sign up to set email alerts
|

Retention of learned predator recognition in embryonic and juvenile rainbow trout

Abstract: Minimizing predation risk, especially for young or naïve individuals, can be achieved by learning to recognize predators. Embryonic learning may optimize survival by allowing for the earliest possible response to predation threats posthatch. However, predatory threats often change over an individual’s lifetime, and using old information can be detrimental if it becomes outdated. Adaptive forgetting allows an individual to discount obsolete information in decision-making and instead emphasize newer, more releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…A large body of research on reversal learning shows that organisms are capable to infer the reliability of cues in nature ( Izquierdo et al 2017 ). Trout, for example, learn to recognize the sight or smell of potential predators ( Behrens et al 2007 ; Horn et al 2019 ). When studying phenotypic plasticity in cases where the optimal response is known to the organism, we study so-called “switch-like” plasticity ( Snell-Rood 2012 ; Frankenhuis et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of research on reversal learning shows that organisms are capable to infer the reliability of cues in nature ( Izquierdo et al 2017 ). Trout, for example, learn to recognize the sight or smell of potential predators ( Behrens et al 2007 ; Horn et al 2019 ). When studying phenotypic plasticity in cases where the optimal response is known to the organism, we study so-called “switch-like” plasticity ( Snell-Rood 2012 ; Frankenhuis et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To conclude, while previous studies on the effects of environmental conditions on fish embryogenesis have mainly focused on abiotic factors such as temperature (Johnston, 2006; Lavery & Cunjak, 2019), we included both temperature and a predator threat. Temperature and predator‐induced effects during embryogenesis may result in adaptive preconditioning, improving the chances for fish to reduce predation risk as juveniles (Horn et al, 2019; Nelson et al, 2013). However, our results showed that there seems to be no straightforward picture of how temperature and predator threat affect growth during the embryonic stage.…”
Section: Discussionmentioning
confidence: 99%
“…Predators both consume prey and induce nonlethal effects on prey physiology and behaviour (McCauley et al, 2011; Stoks et al, 2006). Learned predator recognition during embryogenesis has been reported in teleosts (Horn et al, 2019; Nelson et al, 2013), amphibians (Ferrari & Chivers, 2010; Garcia et al, 2017) and gastropods (Dalesman et al, 2015). For example, rainbow trout ( Oncorhynchus mykiss ) conditioned both to northern pike ( Esox lucius ) odours and conspecific alarm cues during embryogenesis exhibit anti‐predator behaviours as juveniles in the presence of pike (Horn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations